2008
DOI: 10.1186/1757-1626-1-383
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated tuberculosis following the placement of ureteral stents: a case repot

Abstract: BackgroundMiliary tuberculosis occurs as a result of hematogenous dissemination of Mycobacerium tuberculosis. This can occur due to progressive primary infection, reactivation of latent focus with subsequent spread, or rarely via iatrogenic origin.Case presentationThis is a case of 21 year-old woman presented with hydronephrosis and hematuria due to unrecognized renal tuberculosis. She underwent bilateral ureteral stent placement which lead to dissemination of the Mycobateria through the blood causing pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…None of the studies have shown surgery as a risk factor for development of ARDS. However surgery is known to disseminate unrecognized tuberculosis [9]. Thus, D & C possibly led to the development of ARDS in our case with existing 'cryptic miliary TB', which was missed during preoperative evaluation.…”
Section: Introductionmentioning
confidence: 79%
“…None of the studies have shown surgery as a risk factor for development of ARDS. However surgery is known to disseminate unrecognized tuberculosis [9]. Thus, D & C possibly led to the development of ARDS in our case with existing 'cryptic miliary TB', which was missed during preoperative evaluation.…”
Section: Introductionmentioning
confidence: 79%
“…These include human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS), and other causes of immunosuppression such as use of biologicals and immunosuppressive drugs for the treatment of various medical disorders, increasing prevalence of organ transplantation, alcoholism, chronic liver disease, chronic hemodialysis, diabetes mellitus, malignancies, and silicosis. [ 1 2 3 4 5 6 7 ]…”
Section: Epidemiologymentioning
confidence: 99%
“…A few cases have been published, describing dissemination of TB after instrumentations of the renal system. [ 2 10 11 12 ] Other reports have described the disease after surgical intervention in a tuberculous epididymitis,[ 13 ] intraocular TB,[ 14 ] and following intravesical Bacillus Calmette–Guérin (BCG) immunotherapy for transitional cell cancer of the bladder. [ 15 ] Dissemination of TB was also described in the transplantation of organs with unrecognized TB such as infected cadaveric kidney[ 16 ] and homograft valve.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations